Analysis of D2D Communication System Over κ-μ Shadowed Fading Channel - Hussain, Z.; Khan, A. ur R.; Mehdi, H.; Saleem, S. M. A. (Engineering, Technology & Applied Science Research, 2018)
Outage performance of a device-to-device (D2D) communication system in the presence of co-channel interference (CCI) is analyzed in this paper. Channels for the D2D and CCI signals are assumed to be κ-μ shadowed faded. Maximal ratio combining (MRC) and selection combining (SC) techniques are considered to combat fading conditions. Characteristic function (CF) expression of the D2D system in the presence of CCI is presented. Outage probability and success probability expressions are presented for the MRC and SC schemes. These outage probability and success probability expressions are functions of various CCI, path-loss and channel fading parameters. With the help of numerical results, effects of CCI on the performance of D2D communication system under different channel fading and path-loss conditions are discussed.